“Comparative analysis of “Daredevils of Sasun” and “The Song of the Nibelungs” Epics - Arakelyan, Ara; Grigoryan, Vachagan (Bulletin of Yerevan University B: Philology, 2022)
The article deals with the problems of comparative epic studies. The Armenian epic "Sasna Tsrer" and the German epic "The Song of the Nibelungs" have much in common, which is manifested thanks to universal and rare motives. The universal motives are considered to be the miraculous birth of the hero, the marriage and matchmaking of the hero, the magical invulnerability of the hero, the warrior-woman, etc., which are often found in the world epic, as well as in the German and Armenian epics. The semantics of the final episodes of the Armenian and German epics are especially rich from a mythological point of view. In them, the motive reaches its apogee, according to which "The essence of a heroic tale is grief and destruction" (M.Steblin–Kamensky). The end of the "Song of the Nibelungs" symbolizes the end of the Burgundian dynasty. Agravakar (Raven Rock) becomes a multi-valued symbol of the completion of the history of Great Armenia in the epic "Sasna Tsrer". The author also considers the motive of epic guilt, which is rarely found in the world epic, and is of key importance in Armenian and German epics.